2016
DOI: 10.1021/acschembio.6b00398
|View full text |Cite
|
Sign up to set email alerts
|

New Aspercryptins, Lipopeptide Natural Products, Revealed by HDAC Inhibition in Aspergillus nidulans

Abstract: Unlocking the biochemical stores of fungi is key for developing future pharmaceuticals. Through reduced expression of a critical histone deacetylase in Aspergillus nidulans, increases of up to 100-fold were observed in the levels of 15 new aspercryptins, recently described lipopeptides with two non-canonical amino acids derived from octanoic and dodecanoic acids. In addition to two NMR-verified structures, MS/MS networking helped uncover an additional 13 aspercryptins. The aspercryptins break the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…An alternative strategy employs, in a single growth medium, defined chemical or biological agents that model ecological and environmental stimuli. Discrete stimuli found to elicit natural product production include histone deacetylase inhibitors (10,11), exposure to subinhibitory levels of antibiotics (12)(13)(14), selection for spontaneous antibiotic resistance (15,16), low-level metal exposure (17), and mixed microbial culture (18,19). The finding that variations in discrete chemical and biological stimuli can alter secondary metabolite production is consistent with the hypothesis that the role of most natural products is to respond to environmental interactions.…”
supporting
confidence: 67%
“…An alternative strategy employs, in a single growth medium, defined chemical or biological agents that model ecological and environmental stimuli. Discrete stimuli found to elicit natural product production include histone deacetylase inhibitors (10,11), exposure to subinhibitory levels of antibiotics (12)(13)(14), selection for spontaneous antibiotic resistance (15,16), low-level metal exposure (17), and mixed microbial culture (18,19). The finding that variations in discrete chemical and biological stimuli can alter secondary metabolite production is consistent with the hypothesis that the role of most natural products is to respond to environmental interactions.…”
supporting
confidence: 67%
“…6 In a natural product molecular network, these clusters represent molecular families (MFs) putatively synthesized by gene cluster families (GCFs). 7 Molecular networking is a powerful approach that has advanced several natural product-related research projects involving dereplication and quantification, 8 discovery, 9 biosynthesis, 10 and chemical ecology. 11 It has also been integrated as a central component of the Global Natural Products Social (GNPS) molecular networking platform, where dereplication is performed against a large, community-acquired reference library of spectra.…”
mentioning
confidence: 99%
“…However, when using metabolomics to study the knockdown of the HDAC rpdA in Aspergillus nidulans, a simultaneous 100-fold increase in the relative expression levels of 61 compounds and 100-fold decrease in 47 compounds was observed, indicating the unpredictable nature of using pleiotropic strategies [14]. Further investigation revealed that A. nidulans produced several fellutamides with proteasome inhibition and antibiotic activities, and subsequent work uncovered a new class of lipopeptides, the aspercryptins [15].…”
Section: Manipulating Global Transcriptionmentioning
confidence: 99%